Penyuluhan Hukum Perlindungan Korban Penyalahgunaan Narkoba Menurut Hukum Positif Dan Hukum Islam di Panti Rehabilitasi Narkoba Amelia Kecamatan Tanjung Morawa Kabupaten Deli Serdang - Rafiqi; Siti Hawa; Marsella (Universitas Medan Area, 2023)
Drug abuse (Narcotics and dangerous drugs) is an international crime and an extra ordinary crime. Situation Analysis The abuse of narcotics among the younger generation is increasing in Indonesia, deviations in the behavior of young people can endanger future generations of this nation because someone who is addicted to drugs will feel addicted (withdrawal) which results in feelings of discomfort and even feelings of extreme pain in the body. The Problem of Partners in PKM in Drug Rehabilitation Amelia North Sumatra Hamlet IX Jalan Serdang Number 57 Beringin District, Deli Serdang Regency Is Providing Legal Counseling, motivation and solutions for dealing with drug addicts from positive legal aspects and state law. The rise of drug abuse that occurs in Indonesian society has encouraged the government to revise the laws and regulations regarding narcotics, where on October 12, 2009 Law no. 35 of 2009 concerning Narcotics.